MAPKs/AP-1, not NF-κB, is responsible for MCP-1 production in TNF-α-activated adipocytes - Zhang, Xiaoyu; Liu, Zhuangzhuang; Li, Wenjing; Kang, Yuan; Xu, Zhenlu; Li, Ximeng; Gao, Yuan; Qi, Yun (Adipocyte, 2022)
Obesity is associated with the infiltration of monocytes/macrophages into adipose tissue in which MCP-1 plays a crucial role. But the regulatory mechanism of MCP-1 expression in adipocytes is not well defined. Our results demonstrated that TNF-α induced abundant MCP-1 production in adipocytes, including 3T3-L1 pre- (≈ 9 to 18-fold), mature adipocytes (≈ 4 to 6-fold), and primary adipocytes(< 2-fold), among which 3T3-L1 pre-adipocytes showed the best reactiveness. Thus, 3T3-L1 pre-adipocytes were used for the most of following experiments. At the transcriptional level, TNF-α (20 ng/mL) also promoted the mRNA expression of MCP-1. It is well recognized that the engagement of TNF-α with its receptor can trigger both NF-κB and AP-1 signalling, which was also confirmed in our study (5-fold and 2-fold). Unexpectedly and counterintuitively, multiple NF-κB inhibitors with different mechanisms failed to suppress TNF-α-induced MCP-1 production, but rather the inhibitors for any one of MAPKs (JNK, ERK and p38) could do. This study, for the first time, reveals that MAPKs/AP-1 but not NF-κB signalling is responsible for MCP-1 production in TNF-α-activated adipocytes. These findings provide important insight into the role of AP-1 signalling in adipose tissue, and may lead to the development of therapeutical repositioning strategies in metaflammation. Abbreviations: AP-1, activator protein-1; CHX, cycloheximide; IR, insulin resistance; MAPK, mitogen-activated protein kinase; NF-κB, nuclear factor κB; RT-qPCR, quantitative real-time PCR; T2DM, type 2 diabetes mellitus; TRE, triphorbol acetate-response element.